Effectiveness of Antibacterial Surfaces in Osseointegration of Titanium Dental Implants: A Systematic Review - López-Valverde, Nansi (2021)
Titanium (Ti) dental implant failure as a result of infection has been established at 40%, being regarded as one of the most habitual and untreatable problems. Current research is focused on the design of new surfaces that can generate long-lasting, infection-free osseointegration. The purpose of our study was to assess studies on Ti implants coated with different antibacterial surfaces, assessing their osseointegration. The PubMed, Web of Science and Scopus databases were electronically searched for in vivo studies up to December 2020, selecting six studies that met the inclusion criteria. The quality of the selected studies was assessed using the ARRIVE (Animal Research: Reporting of In Vivo Experiments) criteria and Systematic Review Center for Laboratory animal Experimentation's (SYRCLE's) risk of bias tool. Although all the included studies, proved greater osseointegration capacity of the different antibacterial surfaces studied, the methodological quality and experimental models used in some of them make it difficult to draw predictable conclusions. Because of the foregoing, we recommend caution when interpreting the results obtained.